Violence and its Linguistic Framing: An Exploration of Boubacar Boris Diop's Murambi, The Book of Bones and Uwem Akpan's Say You're One of Them. Issue 1 (2nd January 2018) - Onanuga, Ayobami
Summary: Several existing studies have investigated the aesthetics of genocide literature. However, there are few studies on genocide literatures from Nigeria especially as there is still a debate on what constitutes genocide in Nigerian literatures. A comparative study of genocide literature from Rwanda and the arguable genocide narratives from Nigeria will further the discourse of what constitutes genocide in Nigerian literature. This study delves into the examination of the use of violent language in Boubacar Boris Diop's documentation of the Rwandan genocide in Murambi and Uwem Akpan's Say You're One of Them and how this replicates the genocide experiences in the two contexts. The study asserts that the convention of measuring and defining genocide based on the scale of killings subverts the reality of the victims of genocides. It further establishes that Akpan's recreation of ethno-religious killings in Nigeria is in sync with the deployment of language in other established instances of genocide literature.